Optimization of the Light Environment in Vertical Agriculture - Raxmatboy qizi, Muroddinova Farida (American Journal of Biodiversity, 2025)
This article explores the optimization of the light environment in vertical farming systems. It discusses the biological importance of light, the advantages of LED technologies, and methods to ensure optimal plant growth by adjusting spectrum, intensity, and photoperiod. The paper emphasizes the necessity of scientifically grounded lighting strategies for efficient and sustainable vertical agriculture.